O ensino de História e Cultura Indígena nas escolas municipais de São Paulo – 2008 a 2016 - Cardoso, Fernanda Borsatto (2018)
This research has as its objective investigating how teaching History and Indian Culture, proposed by Federal Law nº 11.645/08 is being established in the city of São Paulo inside Elementary Schools, as from the publication. That law altered the article 26 of the "Lei de Diretrizes e Bases da Educação Nacional (LDBEN) from 1996 and made teaching of History and African Culture, Afro-brazilian and Indians compulsory in Elementary Schools all over the country. This research specifically refers to the teaching of History and Indian Culture in Elementary Schools of São Paulo, with the objective of analyzing diverse experiences of Law 11.645/08 introduced by History teachers. From this perspective, the research intends to follow the construction of the curriculum inside classrooms- from ordered curriculum to narrative curriculum- supported by what Ivor F. Goodson (2014) named narrative capital, when the teacher presents oneself as the main character of a story. The narrative capital is known in that way as "the capacity of creating a path which people want to follow" and insert itself on this investigation related to the story of the curriculum, from schools subjects and studies about cultural differences